Evaluation of the incidence of bleeding in patients prescribed rivaroxaban for the treatment and prevention of deep vein thrombosis and pulmonary embolism in UK secondary care: an observational cohort study - Vicki Osborne; Miranda Davies; Debabrata Roy; Saad Shakir; Alison Evans (BMJ Open)
Objectives To evaluate the short-term (12 weeks) safety and utilisation of rivaroxaban prescribed to new-user adult patients for the treatment of deep vein thrombosis and pulmonary embolism and for the prevention of recurrent deep vein thrombosis and pulmonary embolism in a secondary care setting in England and Wales.Design An observational cohort study using the technique of Specialist Cohort Event Monitoring.Setting The Rivaroxaban Observational Safety Evaluation study was conducted across 87 participating National Health Service secondary care trusts in England and Wales.Participants 1532 patients treated with rivaroxaban for the prevention and treatment of deep vein thrombosis/pulmonary embolism from September 2013 to January 2016.Interventions Non-interventional postauthorisation safety study of rivaroxaban.Primary and secondary outcome measures (1) Risk of major bleeding in gastrointestinal, intracranial, and urogenital sites and (2) risk of all major and clinically relevant non-major bleeds.Results Of a total of 4846 patients enrolled in the study from September 2013 to January 2016, 1532 were treated with rivaroxaban for the prevention and treatment of deep vein thrombosis/pulmonary embolism. The median age of the deep vein thrombosis/pulmonary embolism cohort was 63 years, and 54.6% were men. The risk of major bleeding within the gastrointestinal, urogenital and intracranial primary sites was 0.7% (n=11), 0.3% (n=5) and 0.1% (n=1), respectively. The risk of major bleeding in all sites was 1.5% (n=23) at a rate of 8.3 events per 100 patient-years.Conclusions In terms of the primary outcome risk of major bleeding in gastrointestinal, intracranial and urogenital sites, the risk estimates in the population using rivaroxaban for deep vein thrombosis/pulmonary embolism were low (<1%) and consistent with the risk estimated from clinical trial data and in routine clinical practice.Trial registration numbers ClinicalTrials.gov Registry (NCT01871194); ENCePP Registry (EUPAS3979).